Optimizing a nitrogen-supplemented, condensed corn soluble medium for growth of the Polyhydroxyalkanoate producer Pseudomonas putida KT217 - Javers, Jeremy; Gibbons, William; Karunanithy, Chinnadurai (International Journal of Agricultural and Biological Engineering, 2012)
Pseudomonas putida KT217 produces medium-chain-length polyhydroxyalkanoate (mcl-PHA) that is of commercial interest as a biodegradable plastic. To reduce PHA production costs, a less expensive medium to grow P. putida KT217 to a high cell dry weight (CDW) was developed. P. putida KT217 was grown in aerated shake flasks on a condensed corn solubles (CCS) based medium that provided several organic acids and carbohydrates that were utilized for growth. The medium was prepared by adding various amounts of fresh CCS (100-600 g/L, or 34.9-209.4 g/L dry basis) to water and then centrifuging and filtering. The CCS permeate media contained dry matter levels of 28.8-164.9 g/L. The CCS permeate medium containing 108.4 g/L solids produced approximately 6 g CDW/L, at a growth rate of 1.03 per hour, and maximum cell population of 4